Trinidad Co-operative Bank Ltd. - (:unkn) unknown (My University, 2010)
Desrciption printed on the postcard: "Established 1914., the foundation laid on 16th February, 1923 by His Excellency, The Governor, Sir Samuel Herbert, K.C.M.G, K.B.E., R.E. afer being blessed by His Lordship the Bishop, Rt. Rev. Dr. A. H. Anstey."
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Banks and banking--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Bank buildings--Trinidad and Tobago